Faith amid the ruins : the book of Habakkuk - Thomas, Heath A. (Transformative word series, 2016)
"In his commentary on Habakkuk, Heath Thomas provides an accessible introduction to this short but relevant prophetic book. His theological and interpretive essays orient all readers to the riches of this book and its relevance for the Christian life today."-- Back cover.